Potential of Cyanine Derived Dyes in Photodynamic Therapy - Natalia Lange; Wojciech Szlasa; Jolanta Saczko; Agnieszka Chwiłkowska (MDPI AG, 2021)
Photodynamic therapy (PDT) is a method of cancer treatment that leads to the disintegration of cancer cells and has developed significantly in recent years. The clinically used photosensitizers are primarily porphyrin, which absorbs light in the red spectrum and their absorbance maxima are relatively short. This review presents group of compounds and their derivatives that are considered to be potential photosensitizers in PDT. Cyanine dyes are compounds that typically absorb light in the visible to near-infrared-I (NIR-I) spectrum range (750-900 nm). This meta-analysis comprises the current studies on cyanine dye derivatives, such as indocyanine green (so far used solely as a diagnostic agent), heptamethine and pentamethine dyes, squaraine dyes, merocyanines and phthalocyanines. The wide array of the cyanine derivatives arises from their structural modifications (e.g., halogenation, incorporation of metal atoms or organic structures, or synthesis of lactosomes, emulsions or conjugation). All the following modifications aim to increase solubility in aqueous media, enhance phototoxicity, and decrease photobleaching. In addition, the changes introduce new features like pH-sensitivity. The cyanine dyes involved in photodynamic reactions could be incorporated into sets of PDT agents.